Comparative Prevalence of Ectoparasitic Fauna on Birds from Selected Mainland and Island of Sarawak - Raja Nur Atiqah, Raja Azizi; Madinah, Adrus (UNIMAS Publisher., 2019)
A survey of ectoparasitic fauna on birds was conducted in October 2017 until January 2018. The aims of this study were to investigate the ectoparasitic fauna on birds and to compare its prevalence in the selected mainland and island of Sarawak. A series of sampling by using mist-net has been done in Mount Sadong and Satang Besar Island with a total of 1440 hours of sampling effort for each locality. A total of 53 individuals of birds were captured and examined for its ectoparasites. Twenty-one species of ectoparasites were recorded comprising four species of lice and 17 species of mites. Four species of lice and 11 species of mites were detected in Mount Sadong while eight species of mites and no lice were detected in Satang Besar Island. The prevalence of ectoparasites infested on birds in Mount Sadong (33.33%) was higher than Satang Besar Island (17.39%). The p-value (p= 0.474) indicated there was no significant difference between the prevalence of ectoparasites from both localities. The result is important since ectoparasites infestation could affect the survival of birds and has the potential transmission of zoonotic disease.